2010
DOI: 10.1111/j.1600-0714.2009.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary profile and oxidative stress in children and adolescents with cystic fibrosis

Abstract: Cystic fibrosis patients demonstrated altered salivary profile, especially in antioxidant enzymatic and molecular activity, possibly resulting from the oral cavity's ongoing inflammatory and oxidative process. Free radical mechanisms may be involved in CF pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 40 publications
(54 reference statements)
2
53
0
3
Order By: Relevance
“…They protect the mucosa against irritative factors, initiate the formation of the dental pellicle that protects the enamel, facilitate the process of mastication and swallowing, and following carbonates and phosphates, constitute the third buffering system that controls the pH. There is a significant increase in protein concentration among patients suffering from CF which has been observed by Aps et al, Modesto et al and Livnat et al 21,36,37 Peker et al, in turn, have not confirmed such a connection. Sialic acid, which is a component of glycoproteins, performs a protective role for the tissues of the oral cavity.…”
Section: Salivamentioning
confidence: 62%
See 1 more Smart Citation
“…They protect the mucosa against irritative factors, initiate the formation of the dental pellicle that protects the enamel, facilitate the process of mastication and swallowing, and following carbonates and phosphates, constitute the third buffering system that controls the pH. There is a significant increase in protein concentration among patients suffering from CF which has been observed by Aps et al, Modesto et al and Livnat et al 21,36,37 Peker et al, in turn, have not confirmed such a connection. Sialic acid, which is a component of glycoproteins, performs a protective role for the tissues of the oral cavity.…”
Section: Salivamentioning
confidence: 62%
“…[36][37][38] The former enzyme initiates the digestion of starch, and it is also capable of bonding with bacteria and the pellicle. As a result, it may have an impact on the carious process.…”
Section: Salivamentioning
confidence: 99%
“…24 In addition, whole saliva samples in younger CF patients have been found to have higher levels of proteins, antioxidants and uric acid compared to controls. 25 All these salivary changes are thought to be related to the chronic oxidative and inflammatory process activity in the oral cavity of these patients and represent biomarkers that could give more clues about the aetiology and monitoring of CF.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…[77][78][79] Endocrinology. In endocrinology, saliva has proven to be a useful diagnostic tool in measuring the concentration of unconjugated steroid hormones and melatonin, even substituting other biological fluids used until now (such as plasma, serum, and urine).…”
Section: 65mentioning
confidence: 99%